2019
DOI: 10.1177/0739456x19882985
|View full text |Cite
|
Sign up to set email alerts
|

All Paths Leading to the Library: Youth Mobility and Community-Based Planning

Abstract: In the context of a community-based planning process to relocate a neighborhood public library in Madison, Wisconsin, this research examines youth’s everyday mobility to improve their access to public space. Through an analysis of field notes, cognitive maps, and interviews with fifth and eighth graders, researchers find that youth move relatively independently every day while using different place-making strategies. The research also finds that mobility options among youth are racialized experiences with impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Discussions of community development have alternatively focused on community-based and equitable approaches to planning on one hand (Brand 2015; Rosen, O’Neill, and Hutson 2018; Sarmiento and Duarte 2015; Zapata and Bates 2017), or real estate, economic development, and housing policy on the other (Anacker and Niedt 2019; Cabrera and Najarian 2013; Kane and Weber 2016; Morales 2009; Mueller et al 2011). While not mutually exclusive, the two sides of community development’s representation in planning reflects often divergent understandings and approaches to the field that typically emphasize either “community” or “development” in community development practice.…”
Section: Community Development and Planning Educationmentioning
confidence: 99%
“…Discussions of community development have alternatively focused on community-based and equitable approaches to planning on one hand (Brand 2015; Rosen, O’Neill, and Hutson 2018; Sarmiento and Duarte 2015; Zapata and Bates 2017), or real estate, economic development, and housing policy on the other (Anacker and Niedt 2019; Cabrera and Najarian 2013; Kane and Weber 2016; Morales 2009; Mueller et al 2011). While not mutually exclusive, the two sides of community development’s representation in planning reflects often divergent understandings and approaches to the field that typically emphasize either “community” or “development” in community development practice.…”
Section: Community Development and Planning Educationmentioning
confidence: 99%
“…Participatory mapping projects have revealed that youth are sensitive to inequalities in their local environments and able to articulate ways the space around them is racialized around inequities (Goodman et al, 2019; Sarmiento & Duarte, 2019; Teixeira & Zuberi, 2016). Other studies have found that youth who have engaged in critical space mapping become more aware of how their environments create or restrict opportunity through their participation in such activities (Akom et al, 2016; Johnston et al, 2020; Rubel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%